Charge Trapping and Detrapping Behavior of Fluorinated HfO2/SiON Gate Stacked nMOSFET - Chen, Yung-Yu; Hsieh, Chih-Ren (My University, 2010)
The charge trapping and detrapping characteristics of the fluorinated hafnium oxide/ oxynitride (HfO2/SiON) gate stack are investigated. Although incorporation of fluorine in the bulk stack had been proven to eliminate both bulk and interface trap densities due to Hf-F and Si-F bond formation, respectively, the effective trapping barrier of the device with fluorine incorporation (1.29 eV) is deeper than without fluorine incorporation (1.13 eV), indicating that the detrapping ability of the fluorinated devices may limit future fluorine process applications.
Keywords: Charge detrapping; fluorine; HfO2